MXene molecular sieving membranes for highly efficient gas separation - Li Ding (Nature Portfolio, 2018)
Two-dimensional materials show great potential for membrane technologies, but their disordered channels hinder their molecular sieving performance. Here, Wang, Gogotsi and colleagues design a MXene membrane with ordered nanochannels that exhibits an excellent H2/CO2 gas separation performance.